Octogésima Octava Reunión Ordinaria del Comité de Agricultura de la Organización Mundial del Comercio - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
This note describes the main points discussed during the Eighty -eighth Regular Meeting of the Committee on Agriculture of the World Trade Organization (WTO), which the Inter-American Institute for Cooperation on Agriculture (IICA) attended in an observer capacity.